Exploring the impact of classroom climate on music aesthetic literacy in nonmusic majors - Liangliang Zhao; He Jiang; Sri Azra Attan; Ku Faridah Ku Ibrahim; Bo Han (PLoS ONE, 2025)
This study explores the impact of the classroom climate, encompassing both the physical environment (PE) and teacher–student interactions (TSI), on music aesthetic literacy (MAL) among nonmusic-major college students. Utilizing a cross-sectional design and convenience sampling, data were collected from 305 valid respondents enrolled in music aesthetics courses. Pearson correlation and linear regression analyses were conducted to investigate the relationships between PE, TSI, and four MAL dimensions: Habit, Attitude, Knowledge, and Performance and Appreciation Skill (PAS). Results indicate that both PE and TSI influence MAL significantly and positively, with TSI having a stronger impact. Specifically, TSI demonstrated greater effects on Attitude, Habit, Knowledge, and PAS, while PE had a notable impact on Knowledge and Habit but less influence on PAS. Linear regression results revealed that PE and TSI collectively explained 43.6% of the variance in MAL (F(2,302) = 116.635, p < 0.05), underscoring the importance of the classroom climate in shaping students’ music aesthetic literacy. These findings suggest that enhancing TSI and creating favorable PEs can effectively support music education in higher education.